Regulation of the immune system by administering lactic acid bacteria to suppress the effects of aflatoxin B1 in mice (Mus musculus) - Dahliatul Qosimah, Sri Murwani, Indah Amalia Amri, Agri Kaltaria Anisa, Ma. Asuncion Guiang Beltran (Journal of Applied Pharmaceutical Science, 2022)
Aflatoxin B1 (AFB1), which is a toxic compound produced by the filamentous fungus Aspergillus sp., is highly carcinogenic, damages vital organs, and may cause death. Prevention of aflatoxin poisoning through proper food storage and physical treatment is an added cost, thus there is a need to identify alternative methods including treatment with probiotic bacteria. We evaluated the effect of Lactobacillus bulgaricus on activating immune cells in mice exposed to Aflatoxin B1. The study used a post-test control design consisting of five treatment groups including a negative control, positive control, and T1, T2, and T3 groups treated with lactic acid bacteria at doses of 105 colony forming unit (CFU)/ml, 107 CFU/ml, and 109 CFU/ml, respectively, administered on days 7–28 and AFB1 at a dose of 0.2 mg/ kg bw orally on days 15–28. The relative number of lymphocytes consisting of CD11c+transforming growth factorbeta (TGF-β)+, CD4+CD8+, and B220+IgG+, was measured using flow cytometry. The data were analyzed using a one-way analysis of variance test. The results indicated that L. bulgaricus bacteria increased the relative number of CD11c+TGF-β+, B220+IgG+, and CD4+CD8+ cells in mice exposed to the mycotoxin. Lactobacillus bulgaricus may function as an immunostimulator against mycotoxins by inducing the humoral and cellular immune response.
Keywords: Lactic acid bacteria, toxin, fungi, cellular immune, humoral immune